Presentation of a Sedation Standard Using the Example of Transesophageal Echocardiographies (TEE) in Pediatric Outpatients - Sauer, H.; Pfeifer, J.; Gräber, S.; Abdul-Khaliq, H. (Klinische Pädiatrie, 2017)
Introduction Most pediatric patients require deep sedation for a TEE examination. We analyzed the data of our sedation protocols relating to all outpatient TEEs in patients under 18 years of age for the year 2011. On the basis of the data records of a total of 40 patients, we will describe our standard and compare it with the findings of the international literature.Material and Methods In a retrospective analysis, we inspected our sedation protocols in terms of patient-related data, vital parameters, drug applications, occurring complications and necessary interventions as well as nausea and vomiting during the post-sedative monitoring phase.Results In line with our standard, we applied atropine, midazolam, S-ketamine and propofol; complications occurred in 5 patients. They could be handled using simple measures. With regard to the vital parameters, no severe complications occurred. Dizziness was observed in 4 patients during the recovery phase; one patient complained about nausea and vomiting during the first fluid intake. All patients could be discharged 4 h after the termination of sedation.Conclusion Our standard is a practicable and safe procedure for preforming TEE examinations in pediatric outpatients.
Keywords: outpatient examinations; transesophageal echocardiographies (TEE); sedation; standard; pediatric patients